Educational inclusion of students with Autism in Brazil: a literature review - Débora Regina de Paula Nunes; Mariana Queiroz Orrico de Azevedo; Carlo Schmidt (Universidade Federal de Santa Maria (UFSM), 2013)
Brazilian legislation mandates that all children with disabilities have access to general education, including those with autism spectrum disorders (ASD). While the benefits of mainstreamed education have been described in numerous studies, the topic remains controversial, particularly regarding the competence of general schools in addressing the needs of students with ASD. The purpose of this article is to describe what studies published between 2008 and 2013 have revealed about the educational inclusion of people with ASD in Brazil. The results indicate that the access of these students to regular classrooms increased after the popularization of the inclusion paradigm. In spite of this fact, investigations suggest that school personnel have scarce knowledge concerning the syndrome and the educational strategies applied in schools may entail little effect on the learning process of these students.